ANTIBIOTIC SUSCEPTIBILITY IN UROPATHOGEN FROM INTENSIVE CARE PATIENTS WITH URINE CATHETER - Angeline Nifiani M Wibowo; Cucunawangsih Cucunawangsih (Fakultas Kedokteran Universitas Pelita Harapan, 2018)
Background: Multi-Drug Resistance Organisms (MDROs) are defined as organisms that acquired non-susceptibility to more than one antimicrobial agent. Intensive care patients are immune-compromised patients, using catheter and are given broad-spectrum antibiotics. Hence, the chance to develop microbial resistance is high. The aim of this study is to see the etiology and the microbial susceptibility pattern of catheter-associated urinary tract infection patients treated in intensive care.Materials and Methods: The urine samples were taken from catheterized patients admitted to intensive care in Siloam Lippo Village, Tangerang, Indonesia in a one year period from July 2013 until June 2014. We confirmed species identification with Vitex-2 Compact® from Biomérieux, France. The susceptibility of antibiotics is according to Clinical and Laboratory Standard Institute (CLSI). Results: We managed to get 113 urine culture results with mean of age 57.03 ± 18.505 (years). There were 67 males (59.3%) and 46 females (40.70%) that were acquired in the sample. The result of species identification showed that Escherichia coli was the dominant isolate from the urine culture (40.63%), followed by Klebsiella pneumoniae (12.5%). The percentage of MDRO was found to be 71.9%. The antibiotics susceptibility of Escherichia coli for Amoxicilin, Ampicillin/Sulbactam, Ciprofloxacin and Levofloxacin are 50%, 58%, 76% and 75% respectively. Meanwhile the susceptibility against Amikacin and Meropenem are 100% for Escherichia coli and Klebsiella pneumoniae. Conclusion: The proportion of Escherichia coli was the highest among with susceptibility of Meropenem was still high susceptibility for both gram negative and gram positive bacteria.